Toward EFL Students’ Critical Thinking: How Effective Value Line Learning Strategy Is? - Heri Hidayatullah; Siti Syafi’atul Qomariyah (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2023)
Critical thinking in the academic context is considered paramount due to Indonesian government regulations. However, developing such skills needs extraordinary effort. Accordingly, this present research aimed to examine one out of so many strategies called Value Line Learning (VLL) Strategy toward such skills in speaking and writing classes. An experimental research with one group pretest-posttest design was applied aiming at measuring the current strategy for two times (before and after exposing a non-random group of participants to a certain treatment). This study was conducted at MA Nurul Ulum where the population was all students of A class consisting of 21 students due to the total sampling was applied. The instrument of the research was a critical thinking self-assessment questionnaire which has been measured its validity and reliability. The data obtained were then analyzed to calculate the mean, standard deviation, and t-test using SPSS. The findings showed that the mean score of critical thinking in the pre-test was 45.2381 and 78.0952 in the post-test. It meant that there was an improvement in the mean score before and after applying VLL Strategy. Next, The result of testing the hypothesis using a t-test was 38.548 with a level of significant .000. It could be concluded that the Value Line Learning (VLL) Strategy was effective towards the students’ critical thinking skills.